Hf-free semi-Heusler alloy thermoelectric material with high Zehbeck coefficient and preparation method and application of Hf-free semi-Heusler alloy thermoelectric material

By adjusting the Zr element content and preparation process, the problem of improving the thermoelectric performance of Hf-free semi-Hasler alloy is solved, and the Hf-free semi-Hasler alloy thermoelectric material with high Zebeck coefficient and low thermal conductivity is realized, expanding its in-depth space Application potential in areas such as detection.

CN119265470APending Publication Date: 2025-01-07DALIAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411364882.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

How to prepare semi-Hasler alloys with excellent thermoelectric properties without doping Hf is currently lacking effective ways.

Method used

By adjusting the content of Zr elements, introducing different degrees of Zr vacancy, increasing atomic disorder, reducing thermal conductivity and improving Zebeck coefficient, the Hf-free half is prepared by smelting, crushing, grinding and hot pressing sintering in the protective atmosphere, etc. Hasler alloy thermoelectric material.

Benefits of technology

The Zebeck coefficient of the material is significantly improved, and the Zebeck coefficient reaches more than 260μV/K, which improves the thermoelectric performance and reduces the thermal conductivity. It is suitable for use in extreme environments such as deep space exploration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265470A_ABST
    Figure CN119265470A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of thermoelectric materials, and particularly relates to an Hf-free semi-Heusler alloy thermoelectric material with a high Zehbeck coefficient, and a preparation method and application of the Hf-free semi-Heusler alloy thermoelectric material. By adjusting the content of the Zr element, introducing Zr vacancies of different degrees and introducing atom disorder, phonon scattering is enhanced, and the thermal conductivity of the material is remarkably reduced; meanwhile, the Zr vacancy also adjusts the electronic local state, so that the disorder degree of the material is increased, the Zebeck coefficient of the obtained material is greatly improved, and the thermoelectric performance is improved. The invention further provides the Hf-free semi-Heusler alloy thermoelectric material in the scheme or application of the Hf-free semi-Heusler alloy thermoelectric material obtained by the preparation method in the field of deep space exploration. According to the Hf-free semi-Heusler alloy thermoelectric material provided by the invention, the application range of the material is expanded, and the Hf-free semi-Heusler alloy thermoelectric material is suitable for extreme environments such as the deep space exploration field and has potential application value for supplementary power generation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermoelectric materials, and in particular relates to a Hf-free semi-Heusler alloy thermoelectric material with a high Seebeck coefficient, a preparation method and an application thereof. Background Art

[0002] High-temperature thermoelectric materials can be used in extreme environments such as deep space exploration and have potential application value for supplementary power generation. Among them, semi-Heusler alloy is one of the high-temperature thermoelectric materials with application prospects in recent years due to its excellent thermoelectric and mechanical properties.

[0003] Thermoelectric performance is determined by the thermoelectric figure of merit (ZT), ZT = S 2 σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. From the formula, we can see that in order to improve ZT, we need to increase the power factor and reduce the thermal conductivity.

[0004] At present, the main way to improve the thermoelectric properties of semi-Heusler alloys is Hf doping. How to prepare semi-Heusler alloys with excellent thermoelectric properties without doping Hf is basically a blank. Summary of the invention

[0005] The object of the present invention is to provide a Hf-free semi-Heusler alloy thermoelectric material with a high Seebeck coefficient and a preparation method and application thereof. The Hf-free semi-Heusler alloy thermoelectric material provided by the present invention has a high Seebeck coefficient and excellent thermoelectric performance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a Hf-free semi-Heusler alloy thermoelectric material, the chemical composition of which is Zr 1-x oeLh 0.8 Sn 0.2 ; Wherein, the value range of x is 0≤x≤0.10.

[0008] Preferably, in the Hf-free semi-Heusler alloy thermoelectric material, the value range of x is 0.02≤x≤0.10.

[0009] The present invention also provides a method for preparing the Hf-free semi-Heusler alloy thermoelectric material described in the above scheme, comprising the following steps:

[0010] (1) According to the chemical composition of the Hf-free semi-Heusler alloy thermoelectric material, raw materials are smelted in a protective atmosphere to obtain an alloy ingot;

[0011] (2) The alloy ingot is crushed, ground and sintered in sequence to obtain the Hf-free semi-Heusler alloy thermoelectric material.

[0012] Preferably, the raw materials include Zr particles, Co particles, Sb particles and Sn particles; the amount ratio of the Zr particles to the Co particles is 0.9-1.0:1; the amount ratio of the Zr particles to the Sb particles is 0.9-1.0:0.8; the amount ratio of the Zr particles to the Sn particles is 0.9-1.0:0.2.

[0013] Preferably, the smelting includes magnetic levitation smelting; the smelting includes a heating melting stage and a heat preservation stage; the heating rate of the heating melting stage is 30-35°C / s, and the time is based on the melting of all raw materials; the temperature of the heat preservation stage is 1900-2000°C, and the heat preservation time is 20-40s.

[0014] Preferably, the smelting is performed three times or more.

[0015] Preferably, the grinding speed is 300-700 rpm, the grinding time is 10-16 hours, and the target particle size of the grinding is 1-5 μm.

[0016] Preferably, the sintering includes hot pressing sintering; the sintering temperature is 900-1200° C., the pressure is 20-60 MPa, and the holding time is 40-70 min.

[0017] Preferably, the sintering further includes heating; when the sintering temperature is 900-1000°C, the heating is: heating to 280-330°C at a rate of 15-20°C / min, and then heating to 900-1000°C at a rate of 12-16°C / min;

[0018] When the sintering temperature is 1000-1200°C, the heating is: heating to 280-330°C at a rate of 15-20°C / min, then heating to 900-1000°C at a rate of 12-16°C / min, and then heating to 1000-1200°C at a rate of 5-7°C / min.

[0019] The present invention also provides the application of the Hf-free semi-Heusler alloy thermoelectric material described in the above scheme or the Hf-free semi-Heusler alloy thermoelectric material obtained by the preparation method described in the above scheme in the field of deep space exploration.

[0020] The present invention provides a Hf-free semi-Heusler alloy thermoelectric material. The present invention adjusts the content of Zr element, introduces different degrees of Zr vacancies, introduces atomic disorder, enhances phonon scattering, and significantly reduces the thermal conductivity of the material, and the thermal conductivity is not higher than 3.5W m -1 K -1At the same time, Zr vacancies also adjust the localized state of electrons, resulting in an increase in the disorder of the material, which greatly improves the Seebeck coefficient of the resulting material. The Seebeck coefficient is above 260 μV / K, which improves the thermoelectric performance.

[0021] The present invention also provides a method for preparing the Hf-free semi-Heusler alloy thermoelectric material described in the above scheme. The preparation method provided by the present invention has simple steps, convenient operation, low cost, good feasibility, and good economic and social benefits.

[0022] The present invention also provides the application of the Hf-free semi-Heusler alloy thermoelectric material described in the above scheme or the Hf-free semi-Heusler alloy thermoelectric material obtained by the preparation method described in the above scheme in the field of deep space exploration. The Hf-free semi-Heusler alloy thermoelectric material provided by the present invention improves the thermoelectric properties of the semi-Heusler alloy by increasing the atomic disorder, expands the application range of the material, is suitable for use in extreme environments such as the field of deep space exploration, and has potential application value for supplementary power generation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 The electrical conductivity diagram of the Hf-free semi-Heusler alloy thermoelectric material prepared in Examples 1 to 4 and Comparative Example 1;

[0025] Figure 2 The Seebeck coefficient diagram of the Hf-free semi-Heusler alloy thermoelectric material prepared in Examples 1 to 4 and Comparative Example 1;

[0026] Figure 3 The power factor diagram of the Hf-free semi-Heusler alloy thermoelectric material prepared in Examples 1 to 4 and Comparative Example 1;

[0027] Figure 4 The thermal conductivity diagram of the Hf-free semi-Heusler alloy thermoelectric material prepared in Examples 1 to 4 and Comparative Example 1;

[0028] Figure 5 The thermoelectric figure of merit of the Hf-free semi-Heusler alloy thermoelectric material prepared in Examples 1 to 4 and Comparative Example 1;

[0029] Figure 6 Graphs showing the ultra-low temperature electrical conductivity of the Hf-free semi-Heusler alloy thermoelectric materials prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0030] The present invention provides a Hf-free semi-Heusler alloy thermoelectric material, the chemical composition of which is Zr 1-x oeLh 0.8 Sn 0.2 ; Wherein, the value range of x is 0≤x≤0.10.

[0031] In the present invention, in the Hf-free semi-Heusler alloy thermoelectric material, the value range of x is preferably 0.02≤x≤0.10, and specifically can be 0.01, 0.02, 0.04, 0.06, 0.08 or 0.10.

[0032] The present invention also provides a method for preparing the Hf-free semi-Heusler alloy thermoelectric material described in the above scheme, comprising the following steps:

[0033] (1) According to the chemical composition of the Hf-free semi-Heusler alloy thermoelectric material, raw materials are smelted in a protective atmosphere to obtain an alloy ingot;

[0034] (2) The alloy ingot is crushed, ground and sintered in sequence to obtain the Hf-free semi-Heusler alloy thermoelectric material.

[0035] According to the chemical composition of the Hf-free semi-Heusler alloy thermoelectric material, the raw materials are smelted in a protective atmosphere to obtain an alloy ingot. In the present invention, the raw materials preferably include Zr particles, Co particles, Sb particles and Sn particles; the present invention has no special restrictions on the sources of the Zr particles, Co particles, Sb particles and Sn particles, and commercial products well known to those skilled in the art can be used.

[0036] In the present invention, the molar ratio of the Zr particles to the Co particles is preferably 0.9 to 1.0:1, specifically 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1 or 1.0:1.

[0037] In the present invention, the molar ratio of the Zr particles to the Sb particles is preferably 0.9-1.0:0.8, specifically 0.9:0.8, 0.92:0.8, 0.94:0.8, 0.96:0.8, 0.98:0.8 or 1.0:0.8.

[0038] In the present invention, the molar ratio of the Zr particles to the Sn particles is preferably 0.9-1.0:0.2, specifically 0.9:0.2, 0.92:0.2, 0.94:0.2, 0.96:0.2, 0.98:0.2 or 1.0:0.2.

[0039] In a specific embodiment of the present invention, the Zr particles are preferably metal Zr with a purity of preferably 99.95%; the Co particles are preferably metal Co with a purity of preferably 99.98%; the Sb particles are preferably metal Sb with a purity of preferably 99.999%; and the Sn particles are preferably metal Sn with a purity of preferably 99.99%.

[0040] In the present invention, the protective atmosphere is preferably argon; the purity of the argon is preferably above 99.99%, specifically 99.99%, 99.992%, 99.994%, 99.996% or 99.999%.

[0041] In the present invention, the smelting preferably includes magnetic levitation smelting; the smelting preferably includes a heating melting stage and a heat preservation stage; the heating rate of the heating melting stage is preferably 30-35°C / s, specifically 30°C / s, 31°C / s, 32°C / s, 33°C / s, 34°C / s or 35°C / s, and the time is based on the melting of all raw materials; the temperature of the heat preservation stage is preferably 1900-2000°C, specifically 1900°C, 1920°C, 1950°C, 1980°C or 2000°C, and the heat preservation time is preferably 20-40s, specifically 20s, 25s, 30s, 35s or 40s.

[0042] In the present invention, the smelting is preferably performed more than 3 times, specifically 3 times, 4 times, 5 times or 6 times; the smelting equipment is preferably a suspension smelting furnace.

[0043] In the present invention, the smelting preferably further includes cooling; the final temperature of the cooling is preferably room temperature; the cooling rate of the cooling is preferably 55-60°C / S, specifically 55°C / S, 56°C / S, 57°C / S, 58°C / S, 59°C / S or 60°C / s.

[0044] After obtaining the alloy ingot, the present invention sequentially crushes, grinds and sinters the alloy ingot to obtain the Hf-free semi-Heusler alloy thermoelectric material. In the present invention, the crushing preferably includes mechanical crushing; the crushing equipment is preferably a tablet press; the target particle size of the crushing is preferably 1 to 3 mm, specifically 1 mm, 2 mm or 3 mm.

[0045] In the present invention, the grinding speed is preferably 300-700 rpm, specifically 300 rpm, 400 rpm, 500 rpm, 600 rpm or 700 rpm, and the grinding time is preferably 10-16 h, specifically 10 h, 12 h, 14 h or 16 h.

[0046] In the present invention, the grinding preferably includes ball milling; the ball milling preferably includes wet ball milling; the medium of the wet ball milling is preferably anhydrous ethanol; the grinding balls used in the ball milling are preferably tungsten carbide balls; the ball-to-material ratio of the ball milling is preferably 15 to 20:1, specifically 15:1, 16:1, 17:1, 18:1, 19:1 or 20:1.

[0047] In the present invention, the target particle size of the grinding is preferably 1 to 5 μm, specifically 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0048] In the present invention, the sintering preferably includes hot pressing sintering; the sintering temperature is preferably 900-1200°C, specifically 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, the pressure is preferably 20-60MPa, specifically 20MPa, 30MPa, 35MPa, 40MPa, 45MPa, 50MPa or 60MPa, the holding time is preferably 40-70min, specifically 40min, 45min, 50min, 55min, 60min, 65min or 70min; the sintering is preferably carried out in a graphite mold. The present invention can make the alloy more dense and reduce the pores inside the alloy through sintering.

[0049] In the present invention, the sintering preferably further includes heating; when the sintering temperature is 900-1000°C, the heating is preferably: heating to 280-330°C at a rate of 15-20°C / min, and then heating to 900-1000°C at a heating rate of 12-16°C / min; when the sintering temperature is 1000-1200°C, the heating is preferably: heating to 280-330°C at a rate of 15-20°C / min, and then heating to 900-1000°C at a heating rate of 12-16°C / min; when the sintering temperature is 1000-1200°C, the heating is preferably: heating to 280-330°C at a rate of 15-20°C / min The sintering temperature is preferably 1000-1200°C, the temperature is increased to 300°C at a rate of 15°C / min, the temperature is increased to 1000°C at a rate of 14°C / min, and finally the temperature is increased to 1100°C at a rate of 6°C / min.

[0050] The present invention also provides the application of the Hf-free semi-Heusler alloy thermoelectric material described in the above scheme or the Hf-free semi-Heusler alloy thermoelectric material obtained by the preparation method described in the above scheme in the field of deep space exploration.

[0051] The Hf-free semi-Heusler alloy thermoelectric material provided by the present invention improves the thermoelectric performance of the semi-Heusler alloy by increasing the atomic disorder, expands the application range of the material, is suitable for use in extreme environments such as deep space exploration, and has potential application value for supplementary power generation.

[0052] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0053] Example 1

[0054] In this example, Zr 0.9 oeLh 0.8 Sn 0.2 The specific steps of the preparation method are as follows:

[0055] According to the above chemical composition, 6.2629 g of Zr metal particles, 4.4955 g of Co metal particles, 7.4305 g of Sb metal particles and 1.8111 g of Sn metal powder were weighed, wherein the molar ratio of Zr metal particles, Co metal particles, Sb metal particles and Sn metal particles was 0.9:1.0:0.8:0.2;

[0056] The above raw materials were loaded into the crucible of a suspension smelting furnace, heated to a molten state at a heating rate of 30°C / s in an argon (purity 99.99%) atmosphere, maintained at the corresponding temperature for 30s, then cooled to room temperature at a rate of 60°C / s, and repeatedly turned over and smelted for a total of 3 times to obtain an alloy ingot.

[0057] The alloy ingot was mechanically crushed and then wet-milled. The conditions of the wet-milling process were as follows: the medium was anhydrous ethanol, the rotation speed was 500 rpm, the wet-milling time was 12 h, and the powder particle size after wet-milling was 1 to 3 μm. The powder obtained by wet-milling was put into a graphite mold and sintered by hot pressing at a pressure of 40 MPa and a temperature of 1100° C. for 60 min to obtain Zr 0.9 oeLh 0.8 Sn 0.2 .

[0058] Example 2

[0059] In this example, Zr 0.92 oeLh 0.8 Sn 0.2The preparation method is the same as that in Example 1, except that: 6.3578 g of Zr metal particles, 4.4645 g of Co metal particles, 7.3791 g of Sb metal particles and 1.7986 g of Sn metal powder are weighed, wherein the molar ratio of Zr particles, Co particles, Sb particles and Sn particles is 0.92:1.0:0.8:0.2.

[0060] Example 3

[0061] In this example, Zr 0.94 oeLh 0.8 Sn 0.2 The preparation method is the same as that in Example 1, except that: 6.4514 g of Zr metal particles, 4.4338 g of Co metal particles, 7.3285 g of Sb metal particles and 1.7862 g of Sn metal powder are weighed, wherein the molar ratio of Zr particles, Co particles, Sb particles and Sn particles is 0.94:1.0:0.8:0.2.

[0062] Example 4

[0063] In this example, Zr 0.96 oeLh 0.8 Sn 0.2 The preparation method is the same as that in Example 1, except that: 6.5438 g of Zr metal particles, 4.4036 g of Co metal particles, 7.2785 g of Sb metal particles and 1.7741 g of Sn metal powder are weighed, wherein the molar ratio of Zr particles, Co particles, Sb particles and Sn particles is 0.98:1.0:0.8:0.2.

[0064] Comparative Example 1

[0065] In this example, ZrCoSb 0.8 Sn 0.2 The preparation method is the same as that in Example 1, except that: 6.7248 g of Zr metal particles, 4.3444 g of Co metal particles, 7.1806 g of Sb metal particles and 1.7502 g of Sn metal powder are weighed, wherein the molar ratio of Zr particles, Co particles, Sb particles and Sn particles is 1.0:1.0:0.8:0.2.

[0066] Performance Testing

[0067] The electrical performance of the Hf-free semi-Heusler alloy thermoelectric materials prepared in Examples 1 to 4 and Comparative Example 1 was tested using the LSR-3 electrical performance test system. The test curve of electrical conductivity is shown in FIG. Figure 1 As shown, the test curve of the Seebeck coefficient is as follows Figure 2 As shown, the test curve of power factor is as follows Figure 3 As shown. Figures 1 to 3 It can be seen that by reducing the proportion of Zr element, the conductivity of the material decreases slightly, while the Seebeck coefficient increases significantly, and the Seebeck coefficient is above 260μV / K, thereby improving the power factor of the material.

[0068] The thermal diffusion coefficient D of the Hf-free semi-Heusler alloy thermoelectric materials prepared in Examples 1 to 4 and Comparative Example 1 was tested by laser flash method (LFA-457 laser thermal conductivity instrument). The material density ρ measured by the Archimedean drainage method and the formula C p =C ph,H +C D (C ph,H is the harmonic phonon specific heat, C D The heat capacity Cp is calculated by the thermal expansion term (the contribution of the thermal expansion term to the specific heat), and then the total thermal conductivity κ is calculated according to the following formula tot :κ tot =C p The result of Dρ, total thermal conductivity is as follows Figure 4 As shown. Figure 4 It can be seen that with the reduction of Zr element, the degree of atomic disorder increases and the thermal conductivity is greatly reduced.

[0069] Using the formula ZT=S 2 σT / κ tot (S is the Seebeck coefficient of the material, σ is the conductivity of the material, κ tot The thermoelectric merit of the Hf-free semi-Heusler alloy thermoelectric materials prepared in Examples 1 to 4 and Comparative Example 1 was calculated. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that by reducing the content of Zr element, the thermoelectric merit of the obtained semi-Heusler alloy thermoelectric material is greatly improved.

[0070] The ultra-low temperature conductivity of Example 1 and Comparative Example 1 was tested using a comprehensive physical property measurement system (Dynacool-14T). The results are as follows: Figure 6 As shown. Figure 6 It can be seen that by dividing the temperature-dependent resistivity by the minimum resistivity, it can be found that after the Zr content decreases, the minimum resistivity point moves to the right, indicating that the atomic disorder increases.

[0071] It can be seen from the above embodiments that the Hf-free semi-Heusler alloy thermoelectric material provided by the present invention has a higher Seebeck coefficient and a lower thermal conductivity. The Seebeck coefficient is above 260 μV / K and has excellent thermoelectric performance.

[0072] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A Hf-free semi-Heusler alloy thermoelectric material, characterized in that: The chemical composition is Zr 1-x oeLh 0.8 Sn 0.2 ; Wherein, the value range of x is 0≤x≤0.

10.

2. The Hf-free semi-Heusler alloy thermoelectric material according to claim 1, characterized in that: In the Hf-free semi-Heusler alloy thermoelectric material, the value range of x is 0.02≤x≤0.

10.

3. The method for preparing the Hf-free semi-Heusler alloy thermoelectric material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) According to the chemical composition of the Hf-free semi-Heusler alloy thermoelectric material, raw materials are smelted in a protective atmosphere to obtain an alloy ingot; (2) The alloy ingot is crushed, ground and sintered in sequence to obtain the Hf-free semi-Heusler alloy thermoelectric material.

4. The preparation method according to claim 3, characterized in that: The raw materials include Zr particles, Co particles, Sb particles and Sn particles; The amount ratio of the Zr particles to the Co particles is 0.9 to 1.0:1; The amount ratio of the Zr particles to the Sb particles is 0.9-1.0:0.8; The amount ratio of the Zr particles to the Sn particles is 0.9-1.0:0.

2.

5. The preparation method according to claim 3, characterized in that: The smelting includes magnetic suspension smelting; The smelting includes a heating and melting stage and a heat preservation stage; The heating rate in the heating and melting stage is 30-35°C / s, and the time is based on the melting of all the raw materials; The temperature of the insulation stage is 1900-2000° C., and the insulation time is 20-40 seconds.

6. The preparation method according to claim 3 or 5, characterized in that: The smelting is performed for more than 3 times.

7. The preparation method according to claim 3 or 4, characterized in that: The grinding speed is 300-700 rpm and the grinding time is 10-16 hours; The target particle size of the grinding is 1 to 5 μm.

8. The preparation method according to claim 3, characterized in that: The sintering comprises hot pressing sintering; The sintering temperature is 900-1200° C., the pressure is 20-60 MPa, and the heat preservation time is 40-70 minutes.

9. The preparation method according to claim 3 or 8, characterized in that: The sintering process also includes heating up; When the sintering temperature is 900-1000°C, the heating is: heating to 280-330°C at a rate of 15-20°C / min, and then heating to 900-1000°C at a rate of 12-16°C / min; When the sintering temperature is 1000-1200°C, the heating is: heating to 280-330°C at a rate of 15-20°C / min, then heating to 900-1000°C at a rate of 12-16°C / min, and then heating to 1000-1200°C at a rate of 5-7°C / min.

10. Application of the Hf-free semi-Heusler alloy thermoelectric material according to any one of claims 1 to 2 or the Hf-free semi-Heusler alloy thermoelectric material obtained by the preparation method according to any one of claims 3 to 9 in the field of deep space exploration.